Neglected Traumatic Vulvar Hematoma: A Case Report - Pratama, Nicholas; Riani, Mutiara; Mardjuki, Edihan; Darmawan, Budi; Ronny, Ronny (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2024)
Introduction: Vulvar hematoma is a rare condition that can arise from many causes. In serious cases, the patient is hemodynamically unstable and requires immediate treatment. Multiple factors from patients and health care providers impact the outcome. Case Illustration: P0A0 60-year-old woman presented to the outpatient clinic with a painful lump in her vulva for 1 month after trauma and observation in primary care. She had previously consumed anticoagulants for venous insufficiency. Her family’s socioeconomic status was relatively poor. She did not have a complete comprehension of her illness. Physical examination revealed left major labia hematoma with a size of 5 x 10 cm, which was confirmed with ultrasonography. Incision and clot evacuation were performed under general anesthesia and showed a good outcome. Discussion: Vulva is an external part of female genitalia composed of smooth muscle and loose connective tissue with rich vascularization. This organ is prone to hematoma, and there is no consensus published yet. In this patient, the treatment was delayed for 1 month because of a failure to disseminate a clear care plan combined with the patient’s low literacy. Conclusion: Vulvar hematoma is a rare case that can be treated with a conservative, surgical, or embolization approach. Neglected cases can become chronic hematomas that lead to difficulties in diagnosis. A clear care plan should be successfully disseminated to the patient despite many communication challenges to ensure fast and appropriate medical treatment.Hematoma Vulva Traumatik Terbengkalai : Laporan KasusAbstrak Pendahuluan: Hematoma vulva adalah kasus jarang yang dapat timbul karena berbagai macam penyebab. Pada kasus yang berat, pasien dapat mengalami hemodinamik yang tak stabil dan memerlukan tatalaksana secepatnya. Berbagai macam faktor dari pasien dan tenaga kesehatan mempengaruhi hasil pengobatan.Ilustrasi Kasus: Wanita P0A0 usia 60 tahun datang ke poliklinik dengan benjolan yang menyebabkan nyeri pada vulva 1 bulan pasca trauma yang telah diobservasi di pelayanan primer. Pasien sebelumnya mengkonsumsi antikoagulan untuk insufisiensi vena. Sosioekonomi keluarga pasien relatif rendah. Pemeriksaan fisik menunjukkan hematoma labia mayor berukuran 5 x 10 cm yang dikonfirmasi dengan ultrasonografi. Pada pasien ini dilakukan insisi dan evakuasi gumpalan darah dibawah anestesi umum yang menunjukkan hasil yang baik. Diskusi: Vulva adalah organ genitalia eksternal wanita yang tersusun atas otot polos dan jaringan ikat longgar yang kaya vaskularisasi. Organ ini rentan mengalami hematoma dan saat ini belum terdapat konsensus. Penanganan pada pasien ini terlambat selama 1 bulan karena rencana penanganan yang tidak tersampaikan kepada pasien yang memiliki literasi kesehatan rendah. Kesimpulan: Hematoma vulva adalah kasus jarang yang dapat ditangani secara konservatif, pembedahan, maupun embolisasi. Kasus terbengkalai dapat menjadi hematoma kronis yang menyulitkan dalam diagnosis. Rencana penatalaksanaan yang jelas harus diberikan kepada pasien dengan segala kesulitan komunikasi demi tatalaksana yang cepat dan tepat.Kata kunci: hematoma vulva, terbengkalai, pemahaman kesehatan, literasi kesehatan rendah